HEMA in the map of science - Miskolczi Mátyás (Acta Periodica Duellatorum)
This article aims to place HEMA on the map of science. To be able to start this work I have to find an appropriate definition on science and on discipline (field of science). After describing main characters of a discipline I investigate HEMA if it shows this characteristic or can be recognised as an interdisciplinary field. The second question I focus on is the place of this field between disciplines and interdisciplinary topics. For this investigation I review methods of bibliometrics and scientometrics and choose a fitting method to be able to get an answer. I also choose a relevant sample of publications the chosen method can be performed on. After mapping HEMA and having result of the chosen method I try to give a picture on the development of in-field usage of HEMA-related works (how often relevant articles are cited by other HEMA-related articles).